The relationship between jumping performance, isokinetic strength and dynamic postural control in elite youth soccer players - Sliwowski, R.; Grygorowicz, M.; Wieczorek, A.; Jadczak, L. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: The aim of this study was to investigate the relationship between vertical jumping performance, isokinetic strength of knee extensors/flexors, and postural priority and to describe a multiple regression model that accounts for the effects of selected parameters of isokinetic strength and postural priority on vertical jumping performance. METHODS: Thirty-one professional male soccer players, aged from 17 to 20 years, participated in this study (age, mean±SD: 18.6±1.26 years; height: 1.78±0.74 m and weight: 73.1±6.77 kg). The correlations between isokinetic knee strength, jumping performance, and postural control were evaluated using the Pearson correlation coefficient. A linear regression model was used to evaluate the effect of hamstrings and quadriceps peak torque of both legs at 60º/s, total work of both legs at 240º/s, and postural priority on jumping performance. RESULTS: The peak torque of right leg knee flexor (quadriceps) muscles, evaluated at 60º/s speed, showed correlations with counter movement jump, 30 second jumping and squat jump (P=0.005, P=0.003, and P=0.007, respectively). We also observed a strong relationship between counter movement jump and 30 second jumping and peak torque of left leg evaluated at the same speed of 60º/s (P=0.26 and P=0.22, respectively). No significant correlations were found between any of the jumping tests and peak torque of knee extensors of both legs at 60º/s. For the 30 second jumping test, it appears that jumping endurance has a significant relationship with total work of knee flexors for right and left legs at 240º/s. CONCLUSIONS: The results of this study demonstrate practical implications for soccer performance, but further exploration is required.